(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the interactive pedagogical aspects of educational technologies aimed at the development of a culture of independent thinking of future teachers based on interactive teaching of philosophy, problem-based learning and the analysis of problem situations, and interactive methods such as "Blitz-survey", "SWOT-analysis", "Discussion", "FSMU", "Intellectual duel", "Dispute of ideas", which are widely used in practice in developing a culture of independent thinking of future teachers; "Intellectual attack", "Boomerang", "Stairway-stairway".